An Evaluation Framework for End-User Experience in Adaptive Systems - SHARP, MARY; WADE, VINCENT PATRICK; LAWLESS, SEAMUS; MULWA, CATHERINE (My University, 2011)
The evaluation of adaptive and personalised systems is a difficult, complicated and very demanding endeavour due to the complex nature of these systems and the usability issues encountered. This demonstration introduces a web-based framework to support the evaluation of end-user experience in adaptive and personalised systems. This framework has been developed based upon advice from domain experts and a review of evaluation approaches, methodologies and techniques adopted by existing adaptive systems. The benefits of the framework include: i) the provision of an interactive reference and recommendation tool to encourage the evaluation of adaptive systems; ii) the collaborative nature of the framework facilitates the sharing of evaluation information among researchers from diverse communities; iii) the identification of pitfalls in the planning process as well as in data analysis; and iv) the translation of presented information into users language of choice.
PUBLISHED
Keywords: Computer Science and Engineering; Adaptive Systems (EFEx)